INTEGRASI SPIRITUALITAS DAN KEPEMIMPINAN YANG EFEKTIF DALAM LINGKUNGAN KERJA - Julians Henry Asep Supriady; Agnes Wulandari, Mayasari Bilolo, Rinal Sambo Kada, Junita Rina (JOURNAL OF COMMUNITY DEDICATION, 2023)
This study addresses "Integration of Spirituality and Effective Leadership in the Workplace" with the aim of exploring how the application of spiritual values can influence leadership effectiveness within organizations. The research examines various leadership practices that integrate spirituality, such as value-based approaches, support for employee well-being, and social responsibility. The findings indicate that leaders who apply spiritual principles tend to create a more inclusive, positive, and collaborative work environment. Spirituality aids leaders in making more ethical decisions, handling conflicts with empathy, and providing better support to employees. Integrating spirituality into leadership contributes to increased motivation, job satisfaction, and employee performance, while fostering a harmonious and productive organizational culture. The conclusion of this study is that the application of spiritual values in leadership not only enhances leadership effectiveness but also improves overall well-being in the workplace.